Calcium sensitivity of human single muscle fibers following plyometric training - Malisoux, L.; Francaux, M.; Nielens, H.; Renard, P.; Lebacq, J.; Theisen, D. (Medicine & Science in Sports & Exercise, 2006)
Purpose: To study the effect of plyometric training on Ca2+ sensitivity and the influence of troponin T (TnT) isoforms on Ca2+-activation properties in skinned human muscle fibers.